No Indication for APTT Screening in Patients on Oral Anticoagulant Therapy - van der Meer, Felix J. M.; Vos, Hans L.; Rosendaal, Frits R. (Thrombosis and Haemostasis, 1999)
Patients on oral anticoagulant therapy (OAT) may bleed due to a very low factor IX level caused by a mutation at Ala-10 in the propeptide region of the factor IX gene. We evaluated screening of patients on OAT with an APTT to detect patients with this abnormality. In 734 patients an APTT was assessed. Twenty-three patients had a disproportionately prolonged APTT. In these patients the factor IX level, the mutation at Ala-10 and the frequency of bleeding complications were assessed. No severely lowered factor IX levels were found (1 patient with 5% factor IX). No mutations at Ala-10 were found and bleeding complications were not more frequent in these patients. Conclusion: Routine APTT screening of patients on OAT is not useful to detect patients with increased bleeding or with the Ala-10 mutation in the factor IX gene.